2017
DOI: 10.5138/09750185.2087
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS analysis, antimicrobial and Antioxidant Effect of Ethanol Garlic Extract

Abstract: <p align="left"><strong>Aim of the study:</strong> The purpose of this study was to investigate the possibility of garlic extract as a feed additive to prevent and treat <em>Salmonella</em> infection.</p><p align="left"><strong>Methods:</strong> Garlic extracts were prepared from fresh crushed garlic and dissolved in different concentrations of ethanol. Garlic extract (<em>Allium sativum</em>) was analyzed by using gas chromatography-mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Moreover, free radicals such as DPPH and ABTS exhibit scavenging activity and have been used to quantify the antioxidant activity of plant extracts. If the IC 50 value of an extract is lower, that compound or extract is considered to have a stronger antioxidant activity [ 20 ]. According to our results, the IC 50 values of our extract were 56.18 and 22.49 µg/mL for the inhibitory effects of DPPH and ABTS, respectively, which is far less compared with the IC 50 value reported previously by other cultivars of Pyrus ussuriensis Maxim [ 11 , 31 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, free radicals such as DPPH and ABTS exhibit scavenging activity and have been used to quantify the antioxidant activity of plant extracts. If the IC 50 value of an extract is lower, that compound or extract is considered to have a stronger antioxidant activity [ 20 ]. According to our results, the IC 50 values of our extract were 56.18 and 22.49 µg/mL for the inhibitory effects of DPPH and ABTS, respectively, which is far less compared with the IC 50 value reported previously by other cultivars of Pyrus ussuriensis Maxim [ 11 , 31 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABTS contains free radicals in its oxidized form, and it is an electron donor. ABTS ammonium salt (7 mM) and potassium persulfate (2.45 mM) were added to water, and the solution was placed in the dark for 14 h at room temperature where it developed a dark blue color [ 20 ]. In each well of a 96-well plate, 200 µL of 7 mM ABTS solution was added followed by the addition of 10 µL/well of the serially diluted PUE.…”
Section: Methodsmentioning
confidence: 99%
“…Acetic acid, butanoic acid, hexanoic acid and octanoic acid were identified in all yogurt samples, but propanoic acid and gibberellic acid were only detected in samples with garlic paste. Acetic acid, propanoic acid and hexadecanoic acid were previously detected in 74% and 100% ethanol garlic extract by Park et al (2017). It has been reported that gibberellins, produced by plants and necessary for their growth and development, are also produced by various bacteria living with plants (Tien et al, 1979).…”
Section: Volatile Compound Profiles Of the Yogurtmentioning
confidence: 99%
“…disulfide, 1,3-dithiane, dimethyl trisulfide and allyl methyl trisulfide were detected in yogurt sample D1.0, also the high concentration of allyl methyl disulfide and allyl methyl trisulfide was remarkable in the D1.0 and D0.5 samples containing domestic garlic compared I1.0 and I0.5 samples containing imported garlic. Some researchers have suggested that these volatiles in garlic oil may protect the body against the injury caused by radical molecules encountered in daily life (Park et al, 2017). Zhang et al (2016) reported that allyl methyl disulfide may become a supplementary drug used in the selective treatment and prevention of liver injury.…”
Section: Volatile Compound Profiles Of the Yogurtmentioning
confidence: 99%
“…Ginger is native to Southeast Asia Islands, and it was one of the oldest species exported from Asia to Europe (15). Ginger usually has a hot taste and fragrant flavor (16). The volatile oils of ginger rhizome compose 1-3% of the fresh weight, were responsible for the characteristic fragrance and flavor (17).…”
Section: Introductionmentioning
confidence: 99%